2005
DOI: 10.1074/jbc.m411924200
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Escherichia coli topA Mutants Lacking DNA Topoisomerase I

Abstract: The viability of the topA mutants lacking DNA topoisomerase I was thought to depend on the presence of compensatory mutations in Escherichia coli but not Salmonella typhimurium or Shigella flexneri. This apparent discrepancy in topA requirements in different bacteria prompted us to reexamine the topA requirements in E. coli. We find that E. coli strains bearing topA mutations, introduced into the strains by DNA-mediated gene replacement, are viable at 37 or 42°C without any compensatory mutations. These topA ؊… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 50 publications
4
58
2
Order By: Relevance
“…The E. coli strain carrying the deletion of the topA allele without the compensatory mutations has been reported recently [21]. We confirmed that transduction of the DtopA into the MG1655 background was not accompanied by the compensatory mutations in the gyrA or gyrB genes or by any changes in the tolC-par and topB regions of the chromosome (unpublished data).…”
Section: Comparative Overview Of the Individual Strainssupporting
confidence: 70%
“…The E. coli strain carrying the deletion of the topA allele without the compensatory mutations has been reported recently [21]. We confirmed that transduction of the DtopA into the MG1655 background was not accompanied by the compensatory mutations in the gyrA or gyrB genes or by any changes in the tolC-par and topB regions of the chromosome (unpublished data).…”
Section: Comparative Overview Of the Individual Strainssupporting
confidence: 70%
“…These results are consistent with our previously published results for T7 RNA polymerase where the strong T7 RNA polymerase efficiently drove plasmid DNA templates to hypernegatively supercoiled status even when the transcriptional machinery did not couple to translation and membrane insertion . We noticed that these results appear inconsistent with the previously published results showing that plasmid hypernegative supercoiling by E. coli RNA polymerase required the anchoring or insertion of the coupled transcription-translation complex into the cytoplasmic membrane Lynch and Wang, 1993;Ma et al, 1994;Pruss and Drlica, 1986;Stupina and Wang, 2005). However, a careful analysis showed that both situations can be explained by the "twin-supercoiled-domain" model of transcription where the friction force applied to E. coli RNA polymerase is different for promoters with different strengths.…”
Section: Discussioncontrasting
confidence: 56%
“…In this case, in order to generate "twin-supercoileddomains," the transcriptional ensemble has to anchor to the bacterial cytoplasmic membrane through co-transcriptional synthesis of polypeptide encoding membrane proteins to maximize friction resistance. This interpretation explains why TCDS for plasmid pBR322 and its derivatives carrying the P tet promoter depends on the expression of a membrane-insertion tetracycline resistance protein in E. coli topA strains Lynch and Wang, 1993;Ma et al, 1994;Pruss and Drlica, 1986;Stupina and Wang, 2005). For strong promoters, such as P T7A1/O4 and P tac , E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations